1999
DOI: 10.1111/j.1834-7819.1999.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in root canal morphology in simulated curved canals o ver‐instrumented with a variety of stainless steel and nickel titanium files

Abstract: The purpose of this project was to observe the amount of apical and mid-curve transportation produced by a range of nickel titanium (NiTi), titanium alloy and stainless steel (SS) files. Tests were carried out in simulated curved root canals produced in epoxy resin blocks. Seven commercially available file types were tested using sizes 15 to 40. Instrumentation was carried out to 1 mm beyond the apex. Changes in canal dimensions were measured at 10ϫ magnification under a shadowgraph. There were substantial dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…The hand preparation technique was a standardized type, without using step-back, flaring the canal circumferentially, up to a MAF #40. Compared with previous studies which have confirmed that Ni-Ti files cause significantly less transportation and remain more centered at the apical area than stainless steel hand files [7,8,10,11,15,22,24], the results of this study show that this finding cannot be generalized. Nickeltitanium hand instruments, ProFile.04 files and prototype d in fact remain more centered in the middle part of the curvature than stainless steel hand instruments.…”
Section: Canal Shape Deviationcontrasting
confidence: 55%
“…The hand preparation technique was a standardized type, without using step-back, flaring the canal circumferentially, up to a MAF #40. Compared with previous studies which have confirmed that Ni-Ti files cause significantly less transportation and remain more centered at the apical area than stainless steel hand files [7,8,10,11,15,22,24], the results of this study show that this finding cannot be generalized. Nickeltitanium hand instruments, ProFile.04 files and prototype d in fact remain more centered in the middle part of the curvature than stainless steel hand instruments.…”
Section: Canal Shape Deviationcontrasting
confidence: 55%
“…Stainless‐steel reamers, which should be used in a reaming working motion, cause marked transportation or straightening of the canal, especially in canals with ovoid cross‐sections (29, 53–55). Distinct transportation of curved canals was also a consistent finding for stainless‐steel K‐files with a rotational cutting action in combination with a longitudinal filing motion (20, 55–58) (Fig. 7).…”
Section: Instrument Action and Development Of Transportationsupporting
confidence: 72%
“…54,55 However, instruments with active cutting blades must be used with caution in the apical region as overinstrumentation with these instruments is likely to create an apical zip. 56 Some studies have reported that instrument shaft design does not significantly modify canal shapes of similar apical sizes, 57 while others have shown that a thin and flexible shaft will permit larger apical sizes with less aberrations.…”
Section: Impact Of Instrument Design Featuresmentioning
confidence: 99%